Optimizing water and nitrogen management improves maize productivity by regulating root development in the cold semi-arid Songnen plains of Northeast China - Chi, Yu Xin; Muhammad, Ihsan; Ali, Shahid; Shah Jahan, Mohammad; Yang, Li; Zhou, Xun Bo (Frontiers in Plant Science, 2025)
IntroductionWater constraints and excessive nitrogen (N) application hinder root development in spring maize in cold semi-arid regions (CSR), limiting growth and yield. In this study, we focused on the CSR where water scarcity and high fertilizer use are major challenges. Optimizing water-N interactions can enhance root distribution and nutrient uptake, offering a key strategy for improving crop productivity.Materials and methodsTo determine the optimal water-N management strategy under local climatic conditions and evaluate its effects on root physiology and yield performance of spring maize. A two-year field experiment (2020-2021) tested four N application rates (N0: 0 kg ha-1, N100: 100 kg ha-1, N200: 200kg ha-1, N300: 300 kg ha-1) and three soil moisture levels (S1: 40%, S2: 60%, S3: 80% field capacity). Water was managed by maintaining target soil moisture using TDR-based measurements and supplemental irrigation.ResultsCompared with S3-N300, S3-N200 increased plant height (7.89%), stalk thickness (10.48%), and spike position height (5.14%), while substantially boosting root antioxidant enzymes (7.72%), lowering reactive oxygen species (11.81%) and raising K+ (18.22%), Ca2+ (16.35%), Mg2+ (20.01%), and reduced Na+ (3.83%) levels. It also elevated Indole-3-acetic acid (IAA), Gibberellins (GAs), and Zeatin + Zeatin Riboside (Z+ZR) by 45%, 43%, and 30%, respectively. Biomass accumulation rose in spike (11.98%), leaf (23.21%), stalk (16.63%), and grain (6.95%), resulting in 8.01% yield improvement. Structural equation modeling (SEM) showed that water-N interactions explained 94% of the variation in yield, 89% in ion content, 94% in hormones, and 91% in ROS levels.ConclusionThese findings confirm that S3-N200 (80% field capacity + 200 kg N ha-1) treatment improved root function, stress resilience, and nutrient uptake, thereby enhancing growth and yield compared to conventional local practice (>250-300 Kg N ha-1) without optimized water management. Optimizing water-N strategies in North China’s CSR supports sustainable maize production and strengthens agricultural resilience under water-limited conditions.